A 2-DOF Shoulder Exosuit Driven by Modular, Pneumatic, Fabric Actuators - Natividad, Rainier F.; Miller-Jackson, Tiana; Chen-Hua, Raye Yeow (IEEE transactions on medical robotics and bionics, 2021)
The shoulder plays a crucial role in moving the upper limb. It is capable of articulating in three degrees-of-freedom, which enables the arm to perform kinematically complex manipulation actions. Wearable devices targeting the shoulder must be able to emulate its kinematics. Robotic exosuits are an attractive medium to provide shoulder assistance; but current soft robotic actuators feature limited mobility. This work presents a new 2-DOF soft robotic shoulder exosuit that utilizes modular soft actuators that are able to emulate the humerus' movement. The actuator design enables 3-D bending with insignificant resistance. Powered through separated inflation modules, these actuators are configured as two antagonistic pairs that operate in a parallel configuration. The actuator can reach full bending ( > 360^° ) with low pressures ( \mathbf {\mathrm {\sim }}10 kPA). The exosuit's actuators output 11.15N-m of torque at the neutral position, and 4.44 N-m at 90^° shoulder elevation. A test performed on healthy subjects showed that use of the exosuit reduces muscle activation by up to 65% when performing shoulder elevation, and up to 34% when rotating the plane of elevation. The reduction in muscle activation highlights the promising ability of robotic exosuits in supporting arm movements through the entire range of their motion.